Fractal analysis of area-perimeter relationship of some selected countries of the world. (2008)
"Boundaries of six selected countries one from each continent were studied using fractal dimension technique. The Area - Perimeter relation method was used, where land area covered and boundary length of designated countries were measured in the unit of known box size (Box counting). The log-log plots of these variables were obtained and the slopes were measured as h18 required dimensions. Fractal dimensions determined lie between 1.19 and 1.55. The scale size of the maps, and the number of states both had no significant effect (p>0.05) on the fractal dimensions obtained "